The Cross Media Nature of Art and the Cross Media Construction Analysis of Art Theory - Yin, Wuxian (Journal of Theory and Practice of Management Science, 2023)
Art is the main body of art production and appreciation, serving as a bridge between artists and viewers. Together with artists and art connoisseurs, it constructs the coordinates of world art practice and research, breaking the implementation of the work oriented theory in other fields in the context of turning to and cross media, fully demonstrating the interconnectivity between art and enriching the research on art theory, This provides a basis for the cross media construction of art theory. This article explores the existence and transformation of art media from a sociological perspective, analyzes the cross media attributes of art, and explores the theoretical cross media construction model of art, providing reference for relevant research scholars.